Performance : conceito, história e educação - Machado, Ketlim Favero (My University, 2018)
This monograph aims to study the use of the body as a support for artistic expression, a practice that has developed since the beginning of man, and which we call performance today. This is an introductory study on performance art with a panorama about its concept and its different nomenclatures as it happening and the body art. In addition, it presents a performance presentation in Brazil and in the world, from the earliest experiences to the most contemporary productions, with an emphasis on political and social character. In order to contribute to the reflection of the teaching and learning the visual arts, it also presents a study about the importance of performance, such as method and content, basic education for the development of students critical and creative abilities.
Este trabalho teve o objetivo de estudar o uso do corpo como suporte para a expressão artística, prática que se desenvolveu desde os primórdios do homem, e que denominamos, hoje, de performance. Trata-se de um estudo introdutório sobre a arte performática com um breve panorama sobre seu conceito e suas diferentes nomenclaturas como happening e body art. Além disso, apresenta uma introdução histórica da performance no Brasil e no mundo, desde das primeiras experiências até as produções mais contemporâneas, com ênfase no seu caráter político e social. A fim de contribuir para as reflexões do ensino das artes visuais, também apresenta uma estudo sobre a importância da presença da performance, como método e conteúdo, na educação básica para o desenvolvimento das habilidades críticas e criativas dos estudantes.
Keywords: Performance (Arte); História - Performances; Escolas - Performances